The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/1806-9061-2017-0673
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Levels of Lentil by Product on Growth Performance, Carcass Traits and Egg Yield in Quail (Coturnix Coturnix Japonica)

Abstract: The subject of this study was to evaluate the effects of lentil byproduct (LP) on growth performance, carcass traits and egg yield of quail (Coturnix coturnix Japonica). To achieve this goal, a total of 600 0-day-old quail chicks were used. The birds were divided into 5 groups with 3 replicates. The 1 st , 2 nd , 3 rd , 4 th and 5 th groups received 0, 5, 10, 15 and 20% lentil byproduct, respectively. All the diets were prepared as isonitrogenous and isocaloric. As a result of this study, the highest live body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
3
1
1
Order By: Relevance
“…Furthermore, Yalcın et al (1991 reported that the inclusion of lentil byproducts in diets had no adverse effects on the feed consumption and FCR in poultry. In contrast with our results, Sögüt et al (2018) showed that the inclusion of more than 20% lentil byproducts in the diet of turkeys worsened the FCR.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Yalcın et al (1991 reported that the inclusion of lentil byproducts in diets had no adverse effects on the feed consumption and FCR in poultry. In contrast with our results, Sögüt et al (2018) showed that the inclusion of more than 20% lentil byproducts in the diet of turkeys worsened the FCR.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in agree with the results reported by Ciurescu et al (2017) who reported that the inclusion of lentil byproducts in the diet of broilers did not affect the feed consumption or FCR. Besides, the results of our experiment are similar to those obtained by Çabuk et al (2014) and Ayasan et al (2018). Furthermore, Yalcın et al (1991 reported that the inclusion of lentil byproducts in diets had no adverse effects on the feed consumption and FCR in poultry.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In general, the dietary inclusion of lentil byproducts up to 20% did not affect the body weight of quails at and 35 days. Similar finding were reported by who demonstrated that the inclusion of lentils in broilers' diet did not affect their body weight, and by Sögüt et al (2018) who noted that the dietary inclusion of lentils at a 20% level did not affect the body weight of turkeys. Contrary to our results, a negative effect on the body weight of quails was found with the dietary inclusion of more than 20% lentil byproducts (Kanat, 1992).…”
Section: Discussionsupporting
confidence: 87%
“…However, the concentrations of blood parameters can vary depending on factors such as diet, environmental factors, hormonal factors (Donaldson et al, 2017). Furthermore, there is the effect of gender, between males and females, in females there is influence of the reproductive function, as well of the genetics of birds (Ayaşan et al, 2018). However, because of the few studies in relation to blood parameters, it is necessary to carry out more research to assess the lipid concentration in quails.…”
Section: Vasconcelos Et Al (2014) Evaluated the Carcass Characteristi...mentioning
confidence: 99%